Identification of Hydrocarbons Sub-Basin Based on Gravity Data Analysis in Lampung Area - Sarkowi, Muh; Wibowo, Rahmat Catur; Minardi, Suhayat; Arifianto, Indra (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2021)
Gravity Data analyses in Lampung area are carried out to identify potential hydrocarbon sub-basins. The hydrocarbon potential in the Lampung sub-basin is indicated by the presence of hydrocarbon seepage found in Wai Imus, Wai Tahmi, and from oil shown in Ratu-1 and Tujo-1 exploration wells. Spectrum analysis, filtering, gradient, and gravity anomaly modeling determine the presence of potential hydrocarbon sub-basins in the Lampung sub-basin. Our results show that the Bouguer anomaly in the Lampung sub-basin ranges from 0 mGal to 90 mGal. A high anomaly appears in the southern part associated with basement high and a low anomaly in the center area of the western region related to the existence of the large Sumatra fault zone. The Bouguer Anomaly spectrum analysis result shows that basement depth in the Lampung sub-basin is 2400 m to 4400 meters deep. Data analysis of residual Bouguer anomaly, SVD residual Bouguer anomaly, and fault structure identified 18 sub- hydrocarbon potential basins scattered in Way Kanan, Tulang Bawang Barat, Menggala, Mesuji, Terbanggi Besar - Seputih Surabaya (Central Lampung), Sukadana and Labuhan Maringgai (East Lampung) areas. Some volcanic paths were also identified from Ratu-1 well, and Tujo-1 well in the Lampung WKP block. 2.5D modeling results of residual Bouguer anomaly show Kasai, Muara Enim, and Air Benakat, respectively, overburdened rock formations deposited from the top, followed by the Gumai Formation, which acts as a seal formation, while the hydrocarbon reservoirs are from the Baturaja and Talang Akar Formation. Our subsurface depth model has been verified by Ratu-1 and Tujo-1 exploration well.